Strategy and space: a longitudinal case study of broadcasting facilities - Jensen, Per Anker (International Journal of Strategic Property Management, 2011)
The article is based on results from a research project on space strategies and building values, which included a major case study of the development of facilities for the Danish Broadcasting Corporation over time. The focus is to identify, how different space strategies have been implemented in different periods and how these strategies can be related to the general conditions of the corporation. The strategic uncertainty of the corporation is investigated as a main determining factor for changes in space strategy based on theories of the relations between strategy and place. These theories include that corporations follow one of the three generic space strategies: Incrementalism, standardization, and value-based strategy. among the conclusion are, that the space strategies mostly changes between incremental and value-based strategies, but one period of standardization was identified. Furthermore, there is a clear relation between value-based space strategies and the presence of visionary project champions.First Publish Online: 14 Apr 2011